CRIMINOLOGICAL CHARACTERISTICS OF THE PERSONALITY OF A MILITARY SERVICE MEMBER CRIMINAL - Guseynov, Nasir (Revista Inclusiones, 2020)
The article deals with the theoretical and legal foundations of the concept of personality of a military service member criminal. Analysis of existing approaches has shown that the personality of such criminals has a socio-psychological, socio-economic, and moral basis. On the basis of the studied theoretical approaches, as well as the collected factual material, the author concludes that a military service member criminal is a poorly developed person with an unstable psyche, well developed physically, occupying a leading position in an informal army structure (or seeking to), with experience of aggressive behavior and violence. A criminal from the command staff is an established person, often of a choleric temperament, with experience of aggressive behavior and violence, indifferent to the fate of subordinates and the army in general, putting their interests above all else. The leading types of crimes committed by both privates and command staff are shown on the basis of examples from judicial practice. It has been determined that criminals have a close connection with civil life and society living environments. The solution to the problem is seen in a comprehensive analysis and prediction of socio-economic, spiritual, moral, and psychological issues of society and the army. It is important to overcome problems such as corruption and low professional training of military personnel.